Chechen and blood feud: representation of Chechen during the First Chechen War in 1996 Russian film "Prisoner of the Mountain" - Zulkarnain, Dimas Raflyarso; Kaprisma, Hendra (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2023)
There Film is an art that has been widely recognized, from media that is only for entertainment to its use as a propaganda medium. This research will analyze the representation of Chechen ethnicity in the 1996 Russian war drama film titled Кавказский Пленник (Kavkazkij Plenik) ‘Prisoner of the Mountains’. This study will use the Cinema Study method by Boggs and Petrie (2008) to find out the main ideas of the film through plot, background, and characters, as well as cinematography through visualization and dialogue. The theory used is the theory of representation by Stuart Hall (1997). This research aims to show how this Russian film describes the Chechen ethnicity. In the year it was released, in Russia, a war known as the First Chechen War between the Russian Federal Government and the Chechen Separatists still occur. The film depicted the Chechens as a backward and highly religious people that only want to live their lives in peace rather than as enemies of the state, like the usual wartime film.